Exopolysaccharides of Marine Bacteria: Prospects for Use in Medicine - N. N. Besednova; T. P. Smolina; B. G. Andryukov; T. A. Kuznetsova; V. V. Mikhailov; T. N. Zvyagintseva (Антибиотики и Химиотерапия)
The review presents the main directions of biomedical research on exopolysaccharides (EPS) obtained from various species of marine bacteria. EPS are high molecular weight polymers consisting of sugar residues; they are characterized by a large variety of structures, which causes unique biological properties. Numerous data on antioxidant, immunomodulatory, and antitumor activity of EPS are presented. Particular attention is drawn to the antiviral, antibacterial, and inhibitory effect of EPS on the formation of biofilms. Taking into account the wide spectrum of pharmacological activity and low toxicity, these compounds have attracted attention as a potential source of medicinal substances.